Resepsi Mahasiswa Ilmu Al-Qur’an dan Tafsir Fakultas Ushuluddin UIN Jakarta terhadap Pembelajaran Virtual Tahfidz Al-Qur’an - Lilik Ummi Kaltsum (JOURNAL OF QUR'AN AND HADITH STUDIES, 2021)
This article examines the paradigm in the implementation of learning tahfidz al-Qur’an virtually. In conducting this research, the authors interviewed students who had implemented distance education or virtual programs during the pandemic. This paper also evaluates people's culture in learning the Qur’an online. The main purpose of this paper is to prove that technological offerings related to learning the Qur'an require talaqqi-musyafahah between teachers and students. This research is important to do to help or open up insights for the public that the position of the online internet network is only a tool to facilitate learning caused by the Covid-19 pandemic or in certain situations. The reading results must be shown to the teacher to be corrected right or wrong.